Associations between different types of delivery, empathy, aggression, impulsivity and school bullying in children attending public and private schools in Pereira (Colombia) - Julio C. Sánchez; William Martínez; Andrés M. García; Andrés F. Ramírez; Heidy Y. Mesa; Alejandra Kafruni; Paula M. Herrera (Heliyon)
This study aimed to correlate exposure to oxytocin during childbirth with behavioral determinants in teenage students. The Barratt Questionnaire (BQ), the Buss and Perry Aggression Questionnaire (BPAQ) and the Bryant Empathy Index (BEI), respectively measured impulsivity, aggression and empathy; the results were correlated with the roles of school bullying through the Velásquez and Pineda scale. Mothers were asked about birth circumstances.A total of 401 students were included (mean age 12 ± 1 years, 53,9 % were male, 53,3 % were attending a public school). 41,9 % of students had exogenous oxytocin exposure, 40,1 % had physiological oxytocin exposure, and 18 % had no oxytocin exposure. Regarding bullying, 75,1 % of students were classified as observers, 14,2 % were classified as victims, 6 % were classified as intimidators and 4,7 % exhibited an indifferent role. The mean value of the BPAQ was 78 ± 19, for the BEI was 78 ± 10 and for the BQ was 60 ± 10; all values were considered high. There were no significant differences among the type of delivery, sex and bullying roles or the type of delivery, aggressiveness and impulsivity according to sex; however, males had significantly lower empathy scores. There was no significant association between the type of delivery and the risk of assuming a bullying role. A regression model showed a significant association between attending a private school and a lower risk of developing a victim or intimidator role. This study could contribute to a better understanding of the processes involved in behavioral and emotional outcomes after birth, which can help to design prevention strategies to address increasing mental health problems in youth. Furthermore, this study could help emphasize the importance of promoting physiological delivery and find evidence that helps the scientific community design new work to deepen the relationship between oxytocin and behavior.